Komitmen, Self-efficacy, dan Motivasi : Pengaruh Umpan balik dan Insentif Pada Karyawan Non Manajemen - Apriwandi Apriwandi (Jurnal Ilmiah Aset, 2011)
Motivating employees to play an important role in the organization’s success and part of this study indicate a positive relationship between commitment, self-efficacy and motivation. This study tested whether financial incentives and the type of feedback had an influence on commitment and self-efficacy in improving performance through task motivation. In this study, the proposed variables were the dimension of commitment (affective, continuance and normative) and self-efficacy. The contribution of experimental studies in the behavioral accounting literature by investigating how a specific type of performance feedback and performance-based rewards affected three dimensions of commitment and self-efficacy. Also, in the context of research is relatively easy to investigate whether the prediction is valid to use for lower-level employees. This experiment participants consisted of 84 bachelor degree students of Faculty of Economics and Business, Gadjah Mada University. This experimental study resulted that performance feedback and rewards have no effect on the dimensions of commitment and self-efficacy at the lower level employees. Performance feedback was negatively related to the three dimensions of commitment and self-efficacy, whereas performance-based rewards was positively related to one-dimensional normative commitment. In addition, the motivationwas not significantly related to two of the three dimensions of commitment and self-efficacy. Normative commitment was significantly positively related to employee job motivation level. The implications of this research illustrates that control mechanisms do not go increasing the commitment and self-efficacy of employees and increased employee motivation. And the design of incentives and feedback can improve employee performance.